Smart wudhuk / Mohd Anuar Selamat ... [et al.] - Selamat, Mohd Anuar; Mohd Noor, Faridatuljana; Nik Mustaffa, Nik Muhammad Zawawi; Mohd Khairuddin, Ahmad Shafiq; Ramlee, Muhammad Hadi (Universiti Teknologi MARA, Kedah, 2019)
Smart Wudhuk is a design of a water tap control system for pressurized water flows with a smooth, evenly sprayed release of speculative practices. This gentle water spray method can save water use rather than drain water to wudhuk body parts with conventional water tap. Through this method, the quantity of water used in washing ablution members can be reduced and thereby avoids wastage practices. Smart Wudhuk design is unique with automatic water tap water control, smooth and soft spray water output and is equipped with adjustable water tap to facilitate the washing of the wudhuk body parts. In addition, users also have the option of Operation Mode either Normal Mode or Saving Mode. Through the use of this Smart Wudhuk, the practice of wastage of water that has become habitual in the activities of the population can be reduced. The main impact is reducing the cost of water utilities for mosques and surau involved. In addition, domestic water consumption rates can be lowered and assist authorities in managing local water to deal with water supply crisis in areas where water supply is scarce. The Muslim community in this country is also nurtured in order to familiarize what is right and correct what has become commonplace. Smart Wudhuk is targeted to be an option for installation in every mosque or surau throughout Malaysia.